Green Economy Implementation and Green Human Resource Management as Drivers of Green Career Development in a Geothermal Power Unit - Siti Milkaniah Zahrah; Acep Abdul Basit; Irfan Rizki Gumilar (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
The transition toward a green economy requires energy organizations to align sustainable operation with human resource system that prepare employees for longterm green career demands. This study examines the effects of green economy implementation and green human resource management on green career development among employees of PLTP Kamojang PLN Indonesia Power UBP Kamojang. A quantitative explanatory survey was conducted using a saturated sample of all 134 employees of the Kamojang geothermal power unit. Data were collected throught a 39-item questionnaire measured on a five-point Likert scale and analyzed using partial least squares structural equation modeling with SmartPLS 3. The reflective measurement model met the required criteria for convergent validity, discriminant validity, and internal consistency. Green economy implementation had a positive and significant effect on green career development (β = 0.458; t = 9.967; p < 0.001), while green human resource management also had a positive and significant effect (β = 0.446; t = 9.128; p < 0.001). The model explained 45.4% of the variance in green career development. The findings show that sustainable operational practices and environmentally oriented HR systems jointly strengthen career meaning, skill acquisition, professional relationships, and awareness of changing green work demands. The single-site, cross-sectional, self-reported design limits causal inference and broader generalization.